ケイコウ Xセン ブンセキ ソウチ ニヨル ガンセキ ノ テイリョウ カガク ブンセキ:(2)ビリョウ ゲンソ - 本吉, 洋一; モトヨシ, ヨウイチ; 石塚, 英男; イシヅカ, ヒデオ; 白石, 和行; シライシ, カズユキ; Motoyoshi, Yoichi; Ishizuka, Hideo; Shiraishi, Kazuyuki (1996)
P(論文) 国立極地研究所の蛍光X線分析装置(理学電機工業製, RIX3000)による岩石試料中の微量元素(Ba, Co, Cr, Cu, Nb, Ni, Rb, Sr, V, Y, Zn, Zr)の定量化学分析について, その分析条件, 補正法をまとめた。鉱物効果, 粒度効果, 偏析による分析誤差を防ぐために, 試料は, 融剤(Li_2B_4O_7)との希釈率を1 : 5(重量比)としたガラスビードにしてから測定した。スペクトルの重なり補正, X線管からの重元素の妨害補正, さらにpeak-over-back法によるマトリックス補正を行うことによって, 精度のよい分析結果が得られた。 Analytical procedures for trace elements in rocks (Ba, Co, Cr, Cu, Nb, Ni, Rb, Sr, V, Y, Zn, Zr), using an X-ray fluorescence analyzer (RIGAKU RIX3000) at the National Institute of Polar Research, are summarized. Samples are fused with Li_2B_4o_7 (weight proportion of 1 : 5) to prepare glass bead in order to avoid analytical errors caused by mineralogical effect, grain size effect and segregation. The results were satisfied with correcting spectral line overlap, interference X-ray of heavy elements, and matrix effect by means of peak-over-back method. departmental bulletin paper